COLEÇÃO MALACOLÓGICA DA UNIVERSIDADE CATÓLICA DE PERNAMBUCO – UNICAP - Pereira Júnior, Reginaldo Lourenço; Silva, Higor Maciel Pontes da; Silva, Goretti Sônia (Revista Nordestina de Zoologia, 2017)
Brazilian zoological collections are a limitless compilation of essential information that can in the future lead to important discoveries that are still beyond the technological reach of this generation. So, advances in Malacology help to discover of existing species and reinforces the scientific value of biological collections in education, research and extension. The objective was to carry out the inventory and registration of molluscs distribution that are inserted in the malacological collection of Universidade Católica de Pernambuco (UNICAP), which has material preserved in a humid way (Alcohol 70%). Using the specialized literature, species belonging to groups as Gastropoda and Bivalvia were identified and described, highlighting the distribution in Brazil, the characteristics of the shells and the substrata that they inhabit. Relevant information of each species was recorded in electronic spreadsheets. The identification of local species allows the UNICAP collection to be used by other institutions in research, teaching and extension projects.